2017
DOI: 10.23951/1609-624x-2017-4-49-56
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effectiveness of Educational Methods on the Example of Teaching the Probability Theory and Mathematical Statistics

Abstract: Преподавание математических дисциплин в ву-зах России традиционно основывается в большей степени на классических методах обучения  объ-яснительно-иллюстративных (при чтении лекций) и инструктивно-репродуктивных (при проведении се-минарских и лабораторных занятий). При этом пре-подаватель − основное действующее лицо, а обуча-ющиеся либо являются пассивными слушателями, либо пытаются по образцу и подобию воспроизво-дить показанные действия при решении практиче-ских задач. Безусловно, эти методы, когда их приме-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results of pedagogical experiments [20] have shown that playing a business game using probabilistic and statistical methods significantly improves the quality of training, which is confirmed by the results of intermediate testing and final examination grades. Preparation and attitude of students towards a business game is significantly different from their attitude to traditional events (workshops, control and graphic works), which is explained by emergence of a new psychological situation.…”
Section: Resultsmentioning
confidence: 63%
“…Results of pedagogical experiments [20] have shown that playing a business game using probabilistic and statistical methods significantly improves the quality of training, which is confirmed by the results of intermediate testing and final examination grades. Preparation and attitude of students towards a business game is significantly different from their attitude to traditional events (workshops, control and graphic works), which is explained by emergence of a new psychological situation.…”
Section: Resultsmentioning
confidence: 63%